Documentation of polio eradication initiative best practices: Experience from WHO African Region. Issue 43 (10th October 2016) - Okeibunor, Joseph; Nshimirimana, Deo; Nsubuga, Peter; Mutabaruka, Evariste; Tapsoba, Leonard; Ghali, Emmanuel; Kabir, Shaikh Humayun; Gassasira, Alex; Mihigo, Richard; Mkanda, Pascal
Highlights: PEI generated tremendous amount of manpower with diverse public health skills. PEI put systems in place to accelerate the eradication of polio in the Region. Innovations were developed and applied in target delivery of polio vaccines. PEI accumulated lessons and best practices that will benefit larger public health. A protocol developed to document the best practices is presented here. Abstract: Background: The African Region is set to achieving polio eradication. During the years of operations, the Polio Eradication Initiative [PEI] in the Region mobilized and trained tremendous amount of manpower with specializations in surveillance, social mobilization, supplementary immunization activities [SIAs], data management and laboratory staff. Systems were put in place to accelerate the eradication of polio in the Region. Standardized, real-time surveillance and response capacity were established. Many innovations were developed and applied to reaching people in difficult and security challenged terrains. All of these resulted in accumulation of lessons and best practices, which can be used in other priority public health intervention if documented. Methods: The World Health Organization Regional Office for Africa [WHO/AFRO] developed a process for the documentation of these best practices, which was pretested in Uganda. The process entailed assessment of three critical elements [effectiveness, efficiency and relevance] five aspects [ethical soundness, sustainability, involvement of partners, community involvement, and political commitment] of best practices. A scored card which graded the elements and aspects on a scale of 0–10 was developed and a true best practice should score >50 points. Independent public health experts documented polio best practices in eight countries in the Region, using this process. The documentation adopted the cross-sectional design in the generation of data, which combined three analytical designs, namely surveys, qualitative inquiry and case studies. For the selection of countries, country responses to earlier questionnaire on best practices were screened for potential best practices. Another criterion used was the level of PEI investment in the countries. Results: A total of 82 best practices grouped into ten thematic areas were documented. There was a correlation between the health system performances with DPT3 as proxy, level of PEI investment in countries with number of best practice. The application of the process for the documentation of polio best practices in the African Region brought out a number of advantages. The triangulation of data collected using multiple methods and the collection of data from all levels of the programme proved useful as it provided opportunity for data verification and corroboration. It also helped to overcome some of the data challenge.